High thermoelectric power factor of pure and vanadium-alloyed chromium nitride thin films. (September 2021) - Gharavi, M.A.; Gambino, D.; le Febvrier, A.; Eriksson, F.; Armiento, R.; Alling, B.; Eklund, P.
Graphical abstract: Abstract: Chromium-nitride based materials have shown unexpected promise as thermoelectric materials for, e.g., waste-heat harvesting. Here, CrN and (Cr, V)N thin films were deposited by reactive magnetron sputtering. Thermoelectric measurements of pure CrN thin films show a low electrical resistivity between 1.2 and 1.5 × 10 −3 Ωcm and very high values of the Seebeck coefficient and thermoelectric power factor, in the range between 370–430 μV/K and 9–11 × 10 −3 W/mK 2, respectively. Alloying of CrN films with small amounts (less than 15 %) of vanadium results in cubic (Cr, V)N thin films. Vanadium decreases the electrical resistivity and yields power-factor values in the same range as pure CrN. Density functional theory calculations of sub-stoichiometric CrN1-δ and (Cr, V)N1-δ show that nitrogen vacancies and vanadium substitution both cause n-type conductivity and features in the band structure typically correlated with a high Seebeck coefficient. The results suggest that slight variations in nitrogen and vanadium content affect the power factor and offers a means of tailoring the power factor and thermoelectric figure of merit.